Effect of nitrogen and phosphorus applications on intercropping corn-beans - Cecília, Fernando Costa Santa; Ramalho, Magno Antônio Patto; Garcia, João Carlos (Pesquisa Agropecuaria Brasileira, 2014)
In the growing season of 1978/79, field experiments were conducted in two regions of Minas Gerais state, Lavras and Patos de Minas, with the objective of providing informations to the fertilizing recommendations in the corn-beans (Zea mays L.) - (Phaseolus vulgaris L.) intercrop system. The experimental design used was the randomized block according to a scheme of split plot, with four replications. The split plot treatments were a combination of three levels of nitrogen (0-75-150 kg/ha) with three levels of P2O5 (0-150-300 kg/ha). For the bean crop, a significant interaction between the fertilizer level and the arrangement used was found. In the experiment conducted in Lavras, best responses were obtained for P2O5, and in Patos de Minas, for nitrogen. The estimates of levels of fertilizers which garantee bigger profits varied in relation to the arrangement, and the highest values were found in the arrangement where beans and corn were planted on the same line. The results show the possibility of increasing income to producers through the use of modern technologies, even in a traditional practice as that of the intercropping system.